New Food Product Development : From Concept to Marketplace - Fuller, Gordon W. (Florida CRC Press, 2011)
Contents: introduction new food product development; the new product development team: company organization and its influence on new product development; the sources for new product ideas, strategy and the strategists,...
Includes index
Keywords: Công nghệ thực phẩm